REFLEKSI TERHADAP PEMBANGUNAN DAN ANCAMAN GLOBALISASI - sukri sukri (Ath Thariq Jurnal Dakwah dan Komunikasi, 2018)
Development as a paradigm and the theory of social change today is in crisis and fails to apply in various Third World countries. The failure of development in the third world actually occurs in the countries that are considered the most successful and most widely used as examples for other development countries. Namely capitalist countries model of NIC (newly industrialist countries) such as South Korea and Taiwan. Development failures also occur in countries that are modeled as new NIC countries such as Thailand, Malaysia, and Indonesia. Until now the explanation of various crises has not been completed. There is an explanation that blames the regime's corruption factor as an argument for explaining the rapid fall of capitalism in Asia. Nevertheless, a discourse before the fall of Asian capitalism occurred has begun in the wake of an attempt to repair or reform the system of capitalism. As a process of reform, the approach, ideology, and structure of discourse are not much different from the systems, structures and ideologies that are the foundation of development theory. Discourse that is known globalization.